ECOLOGICAL CONDITIONS AND DISTRIBUTION OF GEMOR TREE SPECIES IN CENTRAL AND EAST KALIMANTAN - Adinugroho, Wahyu C.; Sidiyasa, Kade; Rostiwati, Tati; Syamsuwida, Dida (Indonesian Journal of Forestry Research, 2011)
The aim of this study was to determine the ecological conditions and distribution of gemor bark producing tree species at Tuanan village in Kapuas District, Central Kalimantan Province and Long Daliq village in Kutai Barat, East Kalimantan Province. In order to collect adequate vegetation data, several obser vation plots were laid out by using purposive sampling. Primary and secondary data were collected from the plot areas by obser ving directly the habitat and its ecological condition of vegetation. It was revealed that the gemor tree species tended to grow well on the habitats which have a thin layer of peat (< 2 m), pH 3 â 4 and in a humid climatic condition. Â Two gemor bark producing tree species were identidfied in the study areas, namely Nothaphoebe coriacea (Kosterm.) Kosterm. and Â N. umbelliflora Blume. The similarity level of vegetation composition at both sites (Kapuas and Kutai Barat Districts) was low. The tree species richness in the plot areas of Tuanan in Kapuas District, Central Kalimantan (82 species, 57 genera and 28 families) was higher than that found in Long Daliq, Kutai Barat District, East Kalimantan (38 species, 26 genera and 19 families).